2019
DOI: 10.1155/2019/1217838
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Addition of Consolidation Chemotherapy to Standard Cisplatin-Based Chemoradiotherapy in Uterine Cervical Cancer: Matter of Distant Relapse

Abstract: Background. Treatment of advanced uterine cervical cancer has advanced little in the last 15 years. Although two phase III trials showed survival benefit with the addition of consolidation chemotherapy (CT) after cisplatin-based chemoradiotherapy (RTCT), it is not considered standard of care. We aimed to evaluate the benefit of consolidation CT compared to no additional treatment in patients treated with RTCT. Methods. This is a retrospective study including 186 patients with FIGO stage IB2, IIA2, or IIB to IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
(21 reference statements)
0
17
0
Order By: Relevance
“…Currently, cisplatin (DDP)-based concurrent chemoradiotherapy is the standard treatment for locally advanced CC 6 . A study found that consolidation chemotherapy after cisplatin-based chemoradiotherapy can control distant relapse and improve overall survival (OS) and progression-free survival 7 . However, cisplatin resistance remains a serious problem during the treatment of CC, which greatly restricts the clinical application and efficacy of cisplatin 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cisplatin (DDP)-based concurrent chemoradiotherapy is the standard treatment for locally advanced CC 6 . A study found that consolidation chemotherapy after cisplatin-based chemoradiotherapy can control distant relapse and improve overall survival (OS) and progression-free survival 7 . However, cisplatin resistance remains a serious problem during the treatment of CC, which greatly restricts the clinical application and efficacy of cisplatin 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup-analysis of the randomized controlled trial by Duenas-Gonzales et al showed that patients with Stage III–IVA, tumors ≥5 cm and of non-adenocarcinoma histotype had benefitted the most from adjuvant treatment [ 20 ]. The contrary was found in the study by Fabri et al: stage ≥IIIA had a significantly worse overall survival despite adjuvant platinum–pyrimidine in multivariable analysis [ 21 ]. Kim et al found that adjuvant platinum–pyrimidine and tumor characteristics were not significantly related to overall survival and disease-free survival in univariable analyses [ 22 ].…”
Section: Discussionmentioning
confidence: 68%
“…In nine studies, adjuvant systemic therapy consisted of 1–3 cycles cisplatin and a pyrimidine antagonist. This was 5-fluorouracil in five [ 18 , 19 , 22 , 23 , 24 , 35 ], gemcitabine in four studies [ 11 , 20 , 21 , 34 , 37 ]. In 12 studies, adjuvant systemic therapy was 3–6 cycles of a platinum derivate (carboplatin [ 17 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 40 ], cisplatin [ 49 ], cisplatin or carboplatin [ 28 ] or nedaplatin [ 32 ] with a taxane (paclitaxel in 11 [ 17 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 40 , 50 ], docetaxel in 1 [ 49 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with concurrent radiotherapy and chemotherapy, neoadjuvant chemotherapy plus surgery and post-operative supplementary radiotherapy have different complications. Fabri [13] has reported no difference in adverse reactions between neoadjuvant chemotherapy and concurrent chemoradiotherapy. Dang et al [14] compared the complications of concurrent radiotherapy and chemotherapy with that of radiotherapy alone and found that concurrent radiotherapy and cisplatin-based chemotherapy could increase the therapeutic effect in cervical cancer patients and significantly improve the therapeutic benefit without increasing adverse reactions.…”
Section: Discussionmentioning
confidence: 98%